2017
DOI: 10.1007/978-1-4939-6817-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Use of Morpholino Oligomers for Pretargeting

Abstract: Differing from the conventional direct-targeting strategy in which a probe or payload is directly loaded onto a targeting molecule that binds to the native target, pretargeting is an improved targeting strategy. It converts the native target to an artificial target specific for a secondary targeting molecule loaded with the probe or payload (effector). The effector is small and does not accumulate in normal tissues, which accelerates the targeting process and generates high target to nontarget ratios. DNA/cDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[135][136][137][138]140] Later on, Liu and co-workers studied in detail the principles of the pretargeting strategy using morpholino oligomers, as illustrated in Figure 20. [144] In this approach, the chain length and base sequence of the radiolabeled oligomers might have a critical influence on the observed biological performance. For instance, Liu et al demonstrated that by choosing a cytosinefree base sequence, kidney accumulation of a 99m Tc labeled Phosphodiester DNA single strain 5'-biotinTAATACGACTCACTATAGGGAGamine-3' 5'-amineGGTACAGGTCTCACTGTATGACbiotin-3' and respective complements 99m Tc 3' Hexylamine or 5' Hexylamine HYNIC (glucoheptonate) [125] 5'-biotinTAATACGACTCACTATAGGGAGamine-3' and its complement 99m Tc 3' Hexylamine S-Acetyl-NHS-MAG 3 [126] Phosphorothioate (PS) or Phosphodiester DNA single strain 5'-biotinGGTACAGGTCTCACTGTATGACamine-3' 99m Tc 3' Hexylamine HYNIC (tricine) [127] Phosphorothioate (PS) antisense 5'-GCGTGCCTCCTCACTGGC-3' sense 5'-GCCAGTGAGGAGGCACGC-3' 99m Tc 5' Hexylamine HYNIC(tricine) S-Acetyl-NHS-MAG 3 DTPA anhydride [128] antisense 5'-GCGTGCCTCCTCACTGGC-3' sense 5'-GCCAGTGAGGAGGCACGC-3' random 5'-GGGATCGTTCAGAGTCTA-3' cMORF oligomer can be reduced without adversely influencing tumor accumulation using the pretargeting strategy.…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…[135][136][137][138]140] Later on, Liu and co-workers studied in detail the principles of the pretargeting strategy using morpholino oligomers, as illustrated in Figure 20. [144] In this approach, the chain length and base sequence of the radiolabeled oligomers might have a critical influence on the observed biological performance. For instance, Liu et al demonstrated that by choosing a cytosinefree base sequence, kidney accumulation of a 99m Tc labeled Phosphodiester DNA single strain 5'-biotinTAATACGACTCACTATAGGGAGamine-3' 5'-amineGGTACAGGTCTCACTGTATGACbiotin-3' and respective complements 99m Tc 3' Hexylamine or 5' Hexylamine HYNIC (glucoheptonate) [125] 5'-biotinTAATACGACTCACTATAGGGAGamine-3' and its complement 99m Tc 3' Hexylamine S-Acetyl-NHS-MAG 3 [126] Phosphorothioate (PS) or Phosphodiester DNA single strain 5'-biotinGGTACAGGTCTCACTGTATGACamine-3' 99m Tc 3' Hexylamine HYNIC (tricine) [127] Phosphorothioate (PS) antisense 5'-GCGTGCCTCCTCACTGGC-3' sense 5'-GCCAGTGAGGAGGCACGC-3' 99m Tc 5' Hexylamine HYNIC(tricine) S-Acetyl-NHS-MAG 3 DTPA anhydride [128] antisense 5'-GCGTGCCTCCTCACTGGC-3' sense 5'-GCCAGTGAGGAGGCACGC-3' random 5'-GGGATCGTTCAGAGTCTA-3' cMORF oligomer can be reduced without adversely influencing tumor accumulation using the pretargeting strategy.…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…Our choice of MORFs was only based on their better solubility, slightly lower liver accumulation, and easier availability to us (Mang'era et al, 2001). MORF/cMORF pretargeting has been very successful preclinically for both imaging and therapy (Liu et al, 2006, 2008a, 2010a,c, 2011, 2012; Liu, 2017). Very recently, a Sweden group has achieved similar successes using the PNAs (Westerlund et al, 2015, 2018; Honarvar et al, 2016; Altai et al, 2017).…”
Section: Different Pretargeting Mechanismsmentioning
confidence: 99%
“…Today, several pretargeting strategies can be used to combine antibodies and radioligands in vivo; some of them utilize a noncovalent interaction such as streptavidinbiotin [9][10][11], and some utilize the hybridization of complementary oligonucleotides [12,13] or the ability of bispecific antibodies [14,15] to bind an antigen and a radiolabeled hapten. Last but not least, there is the biorthogonal inverse electron demand Diels-Alder (IEDDA) click reaction, which utilizes the fast and highly specific reaction that occurs between a diene, such as 1,2,4,5-tetrazine (Tz), and a dienophile, particularly trans-cyclooctene (TCO), which appears to be seven times more reactive than the cis-cyclooctene (CCO) in the IEDDA reaction [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%